A positive electrode active material and a preparation method thereof

By covering the core surface of the positive electrode active material of the lithium-ion battery, the problem of poor uniformity of the coating structure in the prior art is solved, and the circulation performance and stability of the lithium-ion battery are significantly improved. sex.

CN115832234BActive Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210087505.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-25
Publication Date
2025-02-25
Estimated Expiration
2042-01-25

AI Technical Summary

Technical Problem

The coating structure of the positive electrode active materials of existing lithium-ion batteries has poor uniformity and cannot effectively improve the stability and circulation performance of the ternary materials.

Method used

Fd3m high voltage disordered phase spinel type material is used as the cladding layer, and the core-covered structure is formed by covering the surface with the NCM or LNCM core. The cladding structure is prepared by hydrothermal reaction and sintering processes to ensure uniformity and stability of the cladding layer.

Benefits of technology

The charge and discharge cycle retention rate and DC internal resistance (DCR) of lithium-ion batteries are improved, and the stability and performance uniformity of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115832234B_ABST
    Figure CN115832234B_ABST
Patent Text Reader

Abstract

The present application relates to a positive electrode active material and a preparation method thereof. The present application relates to a positive electrode active material, characterized in that it comprises: a core, the core is NCM or LNCM, and the NCM has the following general formula: LiNi x Co y Mn z O2, wherein x+y+z=1, the LNCM has the following general formula: Li 1.2 Ni x Co y Mn z O2, wherein x+y+z=0.8; and a coating layer having the following general formula: Li a Ni 0.5 Mn 1.5 O4, wherein 0.5≤a≤1.5, wherein the coating layer is coated on the surface of the inner core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to NCM / LNCM coated with Fd3m structure and its preparation method. More specifically, the present application relates to the following aspects: a cathode active material for lithium-ion batteries having a core-shell structure, a lithium-ion battery, and a preparation method for cathode active materials of lithium-ion batteries. Background Art

[0002] The depletion of energy resources has led to significant developments in new energy storage devices. New energy vehicles are now attracting increasing attention. With the development of new energy vehicles and energy storage businesses, the market's requirements for batteries are getting higher and higher. In new energy vehicles and energy storage businesses, lithium-ion batteries are currently widely used battery products. Lithium-ion batteries (LIBs) have high energy ratios, high energy densities, low self-discharge conditions, high working voltages, good cycle stability, and environmental protection characteristics. In addition, lithium-ion batteries also have long cycle lives and better safety than other batteries, and thus have attracted much attention.

[0003] Lithium-ion batteries mainly work by the movement of lithium ions between the positive and negative electrodes. During the charge and discharge process, lithium ions move back and forth between the two electrodes. More specifically, when charging the battery, lithium ions leave the positive electrode and reach the negative electrode through the electrolyte, so that the negative electrode is in a lithium-rich state. On the other hand, the opposite process occurs during discharge. For the positive electrode of a lithium-ion battery, layered Li[Ni x Co y Mn 1-x-y O 2 (0 < x < 1, 0 < y < 1, 0 < 1 - x - y < 1) as the cathode active material of LIBs has been widely studied. Due to its low cost and high capacity, it is considered to be one of the most promising cathode active materials to meet the requirements of new energy vehicles (such as electric vehicles (EVs) and hybrid electric vehicles). However, due to the strong oxidation of the ternary material itself under high voltage and the strong side reaction between the interface and the electrolyte, the abnormal growth of long-cycle DCR and the attenuation of cycle performance occur. To improve the above problems, coating doping is the main improvement method.

[0004] In the prior art, the coating structure adopted is usually a multi-layer structure, and the coating structure therein is a double-layer structure, the first layer being a high-voltage spinel and the other layer being a solid electrolyte. The high-voltage spinel structure in the prior art is usually an ordered structure. This ordered spinel structure has poor stability compared with the disordered spinel material and cannot fully exert the advantage of the coating in improving the stability of the ternary material. In addition, the prior art adopts a sol-gel scheme, resulting in poor uniformity of the formed coating structure and being only applicable to lithium cobalt oxide cores.

[0005] Therefore, there is an urgent need in the art for a coating structure of a core body that has better performance and better uniformity and can be used for positive electrodes of different lithium-ion batteries. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the present application provides a positive electrode active material having a coating layer on the surface, and the coating layer is a Fd3m high voltage disordered phase spinel type material. This Fd3m high voltage disordered phase spinel type material can improve the charge and discharge cycle retention rate of lithium-ion batteries and improve DCR (direct current internal resistance). In addition, this Fd3m high voltage disordered phase spinel type material has better stability than similar materials with ordered structures, and achieves better coating performance.

[0007] More specifically:

[0008] The first aspect of the present application relates to a positive electrode active material, which comprises: a core, wherein the core is NCM or LNCM, and the NCM has the following general formula: LiNi x Co y Mn z O 2 , wherein x+y+z=1, the LNCM has the following general formula: Li 1.2 Ni x Co y Mn z O 2 , wherein x+y+z=0.8, and a coating layer having the following general formula: Li a Ni 0.5 Mn 1.5 O 4 , wherein 0.5≤a≤1.5, wherein the coating layer is coated on the surface of the inner core.

[0009] Through the coating layer structure of the present application, a coating layer structure with better performance and uniformity that can be used for the core of different lithium-ion battery positive electrodes can be achieved. In addition, through the core-coating layer structure of the present application, the charge and discharge cycle retention rate of the lithium-ion battery can be improved, the DCR (direct current internal resistance) can be improved, and better stability can be achieved.

[0010] The second aspect of the present application relates to a method for preparing a positive electrode active material, which comprises the following steps:

[0011] 1) Providing a core of a positive electrode active material, wherein the core is NCM or LNCM, and the NCM has the following general formula: LiNi x Co y Mn z O 2 , wherein x+y+z=1, the LNCM has the following general formula: Li1.2 Ni x Co y Mn z O 2 , where x+y+z=0.8;

[0012] 2) mixing the kernel in step 1), nickel salt and manganese salt in a molar ratio of 1:3, ammonium salt, and deionized water, and stirring with ultrasonic until completely dissolved;

[0013] 3) transferring the mixture solution obtained in step 2) into a reactor for hydrothermal reaction, and obtaining material A after cooling;

[0014] 4) washing the material A obtained in step 3) in a solution of deionized water and alcohol and drying to obtain a core-coating layer precursor structure, wherein the drying temperature is 80-150° C. and the drying duration is 1-24 hours;

[0015] 5) adding a lithium source to the product obtained in step 4) and then sintering to obtain a positive electrode active material having a core-coating layer structure, wherein the coating layer has the following general formula: Li a Ni 0.5 Mn 1.5 O 4 , wherein 0.5≤a≤1.5, wherein the coating layer is coated on the surface of the inner core.

[0016] The coating layer structure prepared by the method of the present application has better uniformity. In addition, the positive electrode active material with a core-coating layer structure prepared by the method of the present application has better stability, can improve the charge and discharge cycle retention rate of the lithium ion battery, and improve DCR (direct current internal resistance).

[0017] The third aspect of the present application relates to a lithium-ion battery, comprising: a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the positive electrode active material described in the first aspect, or the positive electrode active material prepared by the method described in the second aspect. The lithium-ion battery of the present application has an improved charge-discharge cycle retention rate and an improved DCR (direct current internal resistance).

[0018] The fourth aspect of the present application relates to a secondary battery, which comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode active material as described in the first aspect, or the positive electrode active material prepared by the method described in the second aspect. The secondary battery of the present application has an improved charge and discharge cycle retention rate and an improved DCR (direct current internal resistance).

[0019] The fifth aspect of the present application relates to an electric device, which comprises the lithium ion battery as described in the third aspect or the secondary battery as described in the fourth aspect. The electric device of the present application has improved charge-discharge cycle retention rate and improved DCR (direct current internal resistance).

[0020] The sixth aspect of the present application relates to a battery module, which comprises the lithium-ion battery as described in the third aspect or the secondary battery as described in the fourth aspect. The battery module of the present application has an improved charge-discharge cycle retention rate and an improved DCR (direct current internal resistance).

[0021] The seventh aspect of the present application relates to a battery pack, which comprises the lithium-ion battery as described in the third aspect or the secondary battery as described in the fourth aspect. The battery pack of the present application has improved charge and discharge cycle retention rate and improved DCR (direct current internal resistance).

[0022] Explanation of related terms

[0023] Fd3m: A structural space group with a common layered structure. Representative examples include olivine and spinel.

[0024] DCR: DC internal resistance.

[0025] NCM: has the general formula LiNi x Co y Mn z O 2 material, where x+y+z=1.

[0026] LNCM: has the general formula Li 1.2 Ni x Co y Mn z O 2 The main difference between LNCM material and NCM material is the different lithium content between them. LNCM is a material richer in lithium than NCM.

[0027] LFP: lithium iron phosphate.

[0028] These and other features and advantages will become apparent by reading the following detailed description and by reference to the associated drawings.It is to be understood that the foregoing general description and the following detailed description are illustrative only and are not restrictive of the aspects of what is claimed. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a photographic comparison of the disordered coating structure of Example 1 of the present application and the ordered coating structure of the prior art;

[0030] Figure 2is a comparison of the cycle performance of the lithium ion battery of Example 1 of the present application and the lithium ion battery of Comparative Example 1; and

[0031] Figure 3 Schematic diagram of an embodiment of a device using the lithium-ion battery of the present application as a power system. DETAILED DESCRIPTION

[0032] "Scope" disclosed herein is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0033] In this application, if there is no special description, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution. In this application, if there is no special description, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0034] In this application, unless otherwise specified, the terms "include" and "comprising" mentioned herein may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0035] In the description herein, unless otherwise specified, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0036] The first aspect

[0037] The first aspect of the present application relates to a positive electrode active material, which comprises: a core, wherein the core is NCM or LNCM, and the NCM has the following general formula: LiNi x Co y Mn z O 2 , wherein x+y+z=1, the LNCM has the following general formula: Li 1.2 Ni x Co y Mn z O 2 , wherein x+y+z=0.8, and a coating layer having the following general formula: Li a Ni 0.5 Mn 1.5 O 4 , wherein 0.5≤a≤1.5, wherein the coating layer is coated on the surface of the inner core.

[0038] In one embodiment, it relates to the positive electrode active material of the first aspect, wherein 0.8≤a≤1.2, or a=1, for example: 0.8, 0.9, 1.0, 1.1, 1.2, 0.8-1.1, 0.8-1.0, 0.9-1.2, 0.9-1.1, 0.9-1.0, 1.0-1.2, 1.0-1.1, and all point values, ranges, and sub-ranges therebetween.

[0039] In one embodiment, it relates to the positive electrode active material of the first aspect, wherein the thickness of the coating layer is 20nm to 100nm, or the thickness of the coating layer is 20nm to 60nm, or the thickness of the coating layer is 40nm, for example: 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 20-90nm, 20-80nm, 20-70nm, 20-60nm, 20-50nm, 20-40nm, 30-100nm, 30-90nm, 30-80nm, 30-70nm, 30-60nm, 30-50nm, 30-40nm, 40-100nm, 40-90nm, 40-80nm, 40-70nm, 40-60nm, 40-50nm, and all point values, ranges, and sub-ranges therebetween. The coating layer within the above thickness range can provide better performance for the coated core.

[0040] In one embodiment, the positive electrode active material of the first aspect, wherein the weight proportion of the coating layer is 0.7% to 3.3%, or the weight proportion of the coating layer is 1.0% to 2.0%, or the weight proportion of the coating layer is 1.3%, for example: 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.6%, 1.8%, 1.9%, 2.0%, 1.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 0.7-3.2%, 0.7-3.0%, 0.7-2.8%, 0.7-2.6%, 0.7-2.4%, 0.7-2.2%, 0.7-2.0%, 0.7-1.8%, 0.7-1.6%, 0.7-1.4%, 0.9-3.3%, 0.9-3.2%, 0.9-3.0%, 0.9-2.8%, 0. 9-2.6%, 0.9-2.4%, 0.9-2.2%, 0.9-2.0%, 0.9-1.8%, 0.9-1.6%, 0.9-1.4%, 1.1-3.3%, 1.1-3.2%, 1.1-3.0%, 1.1-2.8%, 1.1-2.6%, 1.1-2.4%, 1.1-2.2%, 1.1-2.0%, 1.1-1.8%, 1.1-1.6%, 1.1-1.4%, 1.3-3.3%, 1.3-3.2%, 1.3-3 .0%, 1.3-2.8%, 1.3-2.6%, 1.3-2.4%, 1.3-2.2%, 1.3-2.0%, 1.3-1.8%, 1.3-1.6%, 1.3-1.4%, 1.4-3.3%, 1.4-3.2%, 1.4-3.0%, 1.4-2.8%, 1.4-2.6%, 1.4-2.4%, 1.4-2.2%, 1.4-2.0%, 1.4-1.8%, 1.4-1.6%, and all point values, ranges, and subranges therebetween. For the above weight proportions, a more disordered coating can be achieved with better stability.

[0041] In one embodiment, the positive active material of the first aspect is related, wherein the Dv50 of the positive active material is 1.0 micron to 4.5 microns, or 2.0 microns to 3.5 microns, or 3.0 microns, for example: 1.0 micron, 1.5 micron, 2.0 micron, 2.5 micron, 3.0 micron, 3.5 micron, 4.0 micron, 4.5 micron, 1.0-4 micron, 1.0-3.5 micron, 1.0-3 micron, 1.5-4.5 micron, 1.5-4 micron, 1.5-3.5 micron, 1.5-3 micron, 2.0 to 4.5 micron, 2.0 to 4 micron, 2.0 to 3.5 micron, 2.0 to 3 micron, 3.0 to 4.5 micron, 3.0 to 4 micron, 3.0 to 3.5 micron, and all point values, ranges, and sub-ranges therebetween. For Dv50 within the above range, a more uniform coating can be achieved.

[0042] The second aspect

[0043] The second aspect of the present application relates to a method for preparing a positive electrode active material, which comprises the following steps:

[0044] 1) Providing a core of a positive electrode active material, wherein the core is NCM or LNCM, and the NCM has the following general formula: LiNi x Co y Mn z O 2 , wherein x+y+z=1, the LNCM has the following general formula: Li 1.2 Ni x Co y Mn z O 2 , where x+y+z=0.8;

[0045] 2) mixing the kernel in step 1), nickel salt and manganese salt in a molar ratio of 1:3, ammonium salt, and deionized water, and stirring with ultrasonic until completely dissolved;

[0046] 3) transferring the mixture solution obtained in step 2) into a reactor for hydrothermal reaction, and obtaining material A after cooling;

[0047] 4) washing the material A obtained in step 3) in a solution of deionized water and alcohol and drying to obtain a core-coating layer precursor structure, wherein the drying temperature is 80-150° C. and the drying duration is 1-24 hours;

[0048] 5) adding a lithium source to the product obtained in step 4) and then sintering to obtain a positive electrode active material having a core-coating layer structure, wherein the coating layer has the following general formula: Li a Ni 0.5 Mn 1.5 O 4, wherein 0.5≤a≤1.5, wherein the coating layer is coated on the surface of the inner core.

[0049] In one embodiment, the method for preparing the positive electrode active material of the second aspect, wherein in step 2), the nickel salt and the manganese salt include sulfate, nitrate, chloride, acetate and any combination thereof; and / or the ammonium salt includes ammonia water, ammonium sulfate and any combination thereof. The above soluble salts can help dissolution.

[0050] In one embodiment, the method for preparing a positive electrode active material according to the second aspect, wherein the temperature of the hydrothermal reaction in step 3) is 200-250°C and the duration is 1-48 hours, for example: the temperature is 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 200-240°C, 200-230°C, 200-220°C, 210-250°C, 210-240°C, 210-230°C, 210-220°C, 220-250°C, 220-240°C, 220-230°C, and all point values, ranges, and sub-ranges therebetween; and / or the duration is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours, 30 hours, 31 hours, 32 hours, 33 hours, 34 hours, 35 hours, 36 hours, 37 hours, 38 hours, 39 hours, 40 hours, 41 hours, 42 hours, 43 hours, 44 hours, 45 hours, 46 hours, 47 hours, 48 ​​hours, 1-40 hours, 1-32 hours, 1-24 hours, 8-48 hours, 8-40 hours, 8-32 hours, 8-24 hours, 16-48 hours, 16-40 hours, 16-32 hours, 16-24 hours, 24-48 hours, 24-40 hours, 24-32 hours, and all point values, ranges, and sub-ranges therebetween. For temperatures and durations within the above ranges, the stoichiometric ratios of the compounds desired in the present application can be advantageously achieved.

[0051] In one embodiment, the preparation method of the positive electrode active material of the second aspect, wherein the sintering temperature of step 5) is 800-1500°C, and the duration is 1-12 hours, for example: the temperature is 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, and all point values, ranges, and sub-ranges therebetween; and / or the duration is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, and all point values, ranges, and sub-ranges therebetween. For the temperature and duration within the above range, the stoichiometric ratio of the compound desired to be obtained in the present application can be advantageously achieved.

[0052] In one embodiment, the method for preparing the positive electrode active material of the second aspect, wherein the molar ratio of the product of step 5) to the lithium source is 0.75-0.8, for example: 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, and all point values, ranges, and sub-ranges therebetween. For the above molar ratio, the stoichiometric ratio of the compound desired to be obtained in the present application can be advantageously achieved.

[0053] In one embodiment, the method for preparing the positive electrode active material of the second aspect, wherein the sintering atmosphere in step 5) is oxygen or air. When oxygen or air is used as the sintering atmosphere, the coating layer composition desired in the present application can be stably synthesized.

[0054] The third aspect

[0055] The third aspect of the present application relates to a lithium-ion battery, which comprises: a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the positive electrode active material of the first aspect, or the positive electrode active material prepared by the method of the second aspect.

[0056] The fourth aspect

[0057] The fourth aspect of the present application relates to a secondary battery, which comprises a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the positive electrode active material as described in the first aspect, or the positive electrode active material prepared by the method described in the second aspect.

[0058] The fifth aspect

[0059] A fifth aspect of the present application relates to an electrical device, which comprises a lithium-ion battery as described in the third aspect or a secondary battery as described in the fourth aspect.

[0060] The sixth aspect

[0061] The sixth aspect of the present application relates to a battery module, which comprises the lithium-ion battery as described in the third aspect or the secondary battery as described in the fourth aspect. The battery module of the present application has an improved charge-discharge cycle retention rate and an improved DCR (direct current internal resistance).

[0062] The seventh aspect

[0063] The seventh aspect of the present application relates to a battery pack, which comprises the lithium-ion battery as described in the third aspect or the secondary battery as described in the fourth aspect. The battery pack of the present application has improved charge and discharge cycle retention rate and improved DCR (direct current internal resistance).

[0064] The present invention will be further described below in conjunction with the accompanying drawings, but it should be understood that they are only used to illustrate the present invention rather than to limit the scope of the present invention.

[0065] Attached to this application Figure 1 The SEM photos show that the disordered coating structure of the present invention is smaller in particle size and has a lower crystallinity than the ordered coating structure of the prior art.

[0066] Attached to this application Figure 2 It is the cycle performance of the lithium-ion battery containing the positive electrode active material of Example 1 of the present application. As can be seen from the attached figure, the upper curve is the cycle performance of the battery using the positive electrode of the lithium-ion battery of Example 1 of the present application coated with the FD3M phase spinel type structure with a thickness of 20nm, and the lower curve is the cycle performance of the lithium-ion battery of Comparative Example 1 without coating. It can be seen that after 800 cycles, the product of the present application has significantly better performance. After 1000 cycles, the product of the present application also has significantly better performance.

[0067] Attached to this application Figure 3 Schematic diagram of an embodiment of a device using the lithium-ion battery of the present application as a power system. Specifically, the lithium-ion battery includes: a lithium-ion battery positive electrode, a lithium-ion battery negative electrode, an electrolyte, and a separator separating the lithium-ion battery positive electrode from the lithium-ion battery negative electrode.

[0068] For a lithium-ion battery positive electrode, it includes a positive electrode current collector and a positive electrode active material containing a positive electrode active substance disposed on at least one surface of the positive electrode current collector. For the positive electrode active material, it can be:

[0069] 1) comprising a positive electrode active material as described herein;

[0070] 2) comprising a positive electrode active material prepared by the method described herein; or

[0071] 3) consisting of or substantially consisting of the positive electrode active material described herein.

[0072] The negative electrode of the lithium ion battery includes a negative electrode current collector and a negative electrode material including a negative electrode active material disposed on at least one surface of the negative electrode current collector.

[0073] An example of a device using a lithium-ion battery as a power system is a car, including new energy vehicles, hybrid vehicles, etc., but not limited thereto. For example, various vehicles (including but not limited to mopeds, cars, trucks, aircraft, drones, etc.) can use the lithium-ion battery described herein (which includes the lithium-ion battery negative electrode, lithium-ion battery positive electrode, separator, electrolyte, etc. as described herein).

[0074] The lithium ion battery negative electrode and the active materials of the lithium ion battery negative electrode used in the present application include but are not limited to: natural graphite, artificial graphite, graphene, carbon nanotubes, soft carbon, hard carbon, etc.

[0075] The binders used for the lithium ion battery, lithium ion battery positive electrode, and lithium ion battery negative electrode of the present application include, but are not limited to: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin, etc.

[0076] The conductive materials used for the lithium-ion battery, lithium-ion battery positive electrode, and lithium-ion battery negative electrode of the present application include, but are not limited to: superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0077] The current collectors used for the lithium ion battery, the positive electrode of the lithium ion battery, and the negative electrode of the lithium ion battery of the present application include, but are not limited to, copper foil, silver foil, iron foil, or foils composed of alloys of the above metals. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer, and may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material base layer (such as a base layer made of materials such as polypropylene PP, polyethylene terephthalate PET, polybutylene terephthalate PBT, polystyrene PS, polyethylene PE and copolymers thereof).

[0078] The lithium ion battery positive electrode, the active material of the lithium ion battery positive electrode, and the core of the lithium ion battery positive electrode with a core-coating structure used in the present application include but are not limited to: olivine-structured lithium-containing phosphates, lithium transition metal oxides and their respective modified compounds, for example, examples of lithium transition metal oxides include but are not limited to lithium cobalt oxides (such as LiCoO 2), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O 2 (NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811)), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (LFP)), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon. The lithium ion battery positive electrode, the active material of the lithium ion battery positive electrode, and the core of the lithium ion battery positive electrode with a core-coating structure of the present application preferably include lithium-containing ternary materials (for example, NCM), lithium-rich nickel manganese cobalt materials (for example, LNCM)

[0079] The electrolytes used in the lithium-ion batteries of this application include but are not limited to: LiPF 6 (Lithium hexafluorophosphate), LiBF 4 (lithium tetrafluoroborate), LiClO 4 (Lithium Perchlorate), LiAsF 6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl imide), LiTFSI (lithium bis(trifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2 F 2 (difluorolithium phosphate), LiDFOP (difluorobis(oxalato) phosphate) and LiTFOP (tetrafluorooxalato) phosphate) are one or more. In one embodiment of the present application, the solvent may be selected from one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0080] The separator used in the lithium-ion battery of the present application includes, but is not limited to: one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different. In an embodiment of the present application, the separator is selected from a polyolefin separator, a polyester separator, a polyimide separator, a polyamide separator and a cellulose separator.

[0081] The lithium-ion battery of the present application can be manufactured by a winding process or a stacking process using the lithium-ion battery positive electrode, the lithium-ion battery negative electrode, the electrolyte and the separator described above.

[0082] Example

[0083] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the specific material ratios, process conditions and results described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0084] Example 1

[0085] Step 1: Use the commercially available core material (NCM) purchased from Guangdong Brunp Recycling Technology Co., Ltd.

[0086] Step 2: The commercially available core NCM (0.1 mol) was mixed with Mn(CH 3 COO 2 ·4H 2 O (0.00105 mol), Ni (CH 3 COO 2 ·4H 2O (0.00035 mol), (NH 4 ) 2 S 2 O 8 (0.00105 mol) and (NH 4 ) 2 SO 4 (0.0021 mol) was added into a beaker and ultrasonically stirred until completely dissolved. The weight ratio of the obtained coating layer was 0.65%.

[0087] Step 3: The mixture solution obtained in step 2 was transferred to a reactor for hydrothermal reaction at 220° C. for 24 hours.

[0088] Step 4: The product obtained in step 3 was washed and dried in a solution of excess deionized water and ethanol at 100°C for 12 hours to obtain a core-coating layer precursor structure, namely NCM (LiNi 0.6 Co 0.2 Mn 0.2 O 2 )-Ni 0.67 Mn 2 O 4 .

[0089] Step 5: Sinter the core-coating layer precursor structure obtained in step 4 with LiOH at a molar ratio of 0.75:1 at 900°C for 1 hour, and then at 700°C for 1 hour. A positive electrode active material having a core-coating layer structure is obtained, wherein the coating layer has the following general formula: Li a Ni 0.5 Mn 1.5 O 4 , where a=1, wherein the coating layer is coated on the surface of the core

[0090] Example 2

[0091] Except step 2 is to mix the NCM (0.1 mol) obtained in step 1-2 with Mn(CH 3 COO 2 ·4H 2 O (0.0021 mol), Ni(CH 3 COO 2 ·4H 2 O (0.0007 mol), (NH 4 ) 2 S 2 O 8 (0.0021 mol) and (NH 4 ) 2 SO 4(0.0042 mol) was added to a beaker and ultrasonically stirred until completely dissolved. The same method as in Example 1 was used except that the weight ratio of the coating layer was 1.3%.

[0092] Example 3

[0093] Except step 2, the commercially available core NCM (0.1 mol) and Mn(CH 3 COO 2 ·4H 2 O (0.00315 mol), Ni (CH 3 COO 2 ·4H 2 O (0.00105 mol), (NH 4 ) 2 S 2 O 8 (0.00315 mol) and (NH 4 ) 2 SO 4 (0.0063 mol) was added to a beaker and ultrasonically stirred until completely dissolved. The preparation was carried out in the same manner as in Example 1 except that the weight ratio of the coating layer was 1.95%.

[0094] Example 4

[0095] Except step 2, the commercially available core NCM (0.1 mol) and Mn(CH 3 COO 2 ·4H 2 O (0.00426 mol), Ni(CH 3 COO 2 ·4H 2 O (0.00142 mol), (NH 4 ) 2 S 2 O 8 (0.00426 mol) and (NH 4 ) 2 SO 4 (0.00853 mol) was added to a beaker and ultrasonically stirred until completely dissolved. The same method as in Example 1 was used except that the weight ratio of the coating layer was 2.6%.

[0096] Example 5

[0097] Except step 2, the commercially available core NCM (0.1 mol) and Mn(CH 3 COO 2 ·4H 2 O (0.00534 mol), Ni (CH 3 COO2 ·4H 2 O (0.00179 mol), (NH 4 ) 2 S 2 O 8 (0.00534 mol) and (NH 4 ) 2 SO 4 (0.0106 mol) was added to a beaker and ultrasonically stirred until completely dissolved. The same method as in Example 1 was used except that the weight ratio of the coating layer was 3.25%.

[0098] Comparative Example 1

[0099] The commercially available product inner core (NCM) purchased from Guangdong Brunp Recycling Technology Co., Ltd. is used without the coating layer of the present application.

[0100] The positive electrode active materials obtained in the above Examples 1-5 and Comparative Example 1 were made into secondary batteries for performance testing. The test results are shown in Table 1 below.

[0101]

Battery capacity retention rate test

[0102] The positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were mixed in a solvent N-methylpyrrolidone (NMP) at a ratio of 8:1:1, and the mixture was stirred and mixed to obtain a positive electrode slurry. The coating thickness is shown in Table 1 below. The positive electrode slurry was evenly coated on an aluminum foil, and then dried and cold pressed to obtain a positive electrode sheet.

[0103] Artificial graphite as a negative electrode active material, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as a binder, and carbon methyl cellulose sodium (CMC) as a thickener are fully stirred and mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on a copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0104] A porous polymer film made of polyethylene (PE) is used as the isolation membrane.

[0105] The electrolyte is 1mol / L LiPF 6 / (ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC)) (volume ratio 1:1:1).

[0106] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, the electrolyte is injected and packaged to obtain a secondary battery.

[0107] At 25°C, the secondary battery prepared above is charged to 4.4V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4.4V, left for 5 minutes, and then discharged to 2.0V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time. The battery capacity retention rate after each cycle is Pn = Cn / C0*100%. The 1000 point values ​​of P1, P2...P1000 are used as the ordinate, and the corresponding number of cycles is used as the abscissa to obtain a curve of the capacity retention rate of the lithium-ion battery and the number of cycles.

[0108] During the test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ... the 1000th cycle corresponds to n=1000. The battery capacity retention rate data corresponding to Example 1 in Table 1 is the data measured after 1000 cycles under the above test conditions, that is, the value of P1000.

[0109]

DCR test

[0110] The secondary battery prepared above was charged to 4.4V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage of 4.4V. The battery was then discharged to 50% SOC, left to stand for 5 minutes, and the voltage V1 was recorded. The battery was then discharged at a current of 4C for 10s, and the voltage V2 was recorded. The voltage (V2-V1) / I is the DCR.

[0111]

Storage gas production test

[0112] Arrange a pipeline along the sealing nail welding hole of the secondary battery prepared as above. The diameter of the pipeline is the same as that of the sealing nail hole. Connect the oil gauge along the end of the pipeline. Fix the battery with 2 aluminum plates. The initial clamp force is set to 3000N. Calibrate it three times, each time with an interval of 15 minutes. Then fully charge the battery to 100% SOC. The temperature of all cells needs to be monitored and the oil gauge pressure is recorded every day.

[0113] Table 1

[0114]

[0115]

[0116] It can be seen from Table 1 above that for Comparative Example 1 in which the positive electrode active material has no coating structure, its DCR after 1000 cycles increases significantly. Although Examples 1-5 of the present application are coated with coating materials, the discharge capacity can be kept basically the same. In addition, the DCR of Examples 1-5 of the present application only slightly increased after 1000 cycles. On the other hand, referring to the gas production performance results, it can be seen that the gas production of the lithium ion batteries of Examples 1-5 of the present application is significantly lower than that of Comparative Example 1.

[0117] Although the present invention has been described in detail for the purpose of clarity and understanding, after reading this application specification, those skilled in the art will understand that various modifications and changes can be made to the present invention without departing from the spirit and essence of the present invention, and these modifications and changes all fall within the scope of the attached claims and their equivalents.

Claims

1. A positive electrode active material, characterized in that: include: The core is NCM or LNCM, and the NCM has the following general formula: LiNi x Co y Mn z O2, wherein x+y+z=1, the LNCM has the following general formula: Li 1.2 Ni x Co y Mn z O2, where x+y+z=0.8, and The coating layer has the following general formula: LiaNi 0.5 Mn 1.5 O4, wherein 0.5≤a≤1.5, wherein the coating layer is coated on the surface of the core, the coating layer is a Fd3m high voltage disordered phase spinel type material, and the thickness of the coating layer is 20nm to 100nm.

2. The positive electrode active material according to claim 1, characterized in that 0.8≤a≤1.2。 3. The positive electrode active material according to claim 1, characterized in that a=1。 4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The coating layer has a thickness of 20 nm to 60 nm.

5. The positive electrode active material according to any one of claims 1 to 3, characterized in that The thickness of the coating layer is 40 nm.

6. The positive electrode active material according to any one of claims 1 to 3, characterized in that The weight ratio of the coating layer is 0.7% to 3.3% relative to the total weight of the positive electrode active material.

7. The positive electrode active material according to any one of claims 1 to 3, characterized in that The weight ratio of the coating layer is 1.0% to 2.0% relative to the total weight of the positive electrode active material.

8. The positive electrode active material according to any one of claims 1 to 3, characterized in that The weight ratio of the coating layer is 1.3% relative to the total weight of the positive electrode active material.

9. The positive electrode active material according to any one of claims 1 to 3, characterized in that The Dv50 of the positive electrode active material is 1.0 micrometer to 4.5 micrometers.

10. The positive electrode active material according to any one of claims 1 to 3, characterized in that The Dv50 of the positive electrode active material is 2.0 micrometers to 3.5 micrometers.

11. The positive electrode active material according to any one of claims 1 to 3, characterized in that The Dv50 of the positive electrode active material is 3.0 microns.

12. A method for preparing a positive electrode active material, characterized in that: The steps include: 1) Providing a core of a positive electrode active material, wherein the core is NCM or LNCM, and the NCM has the following general formula: LiNi x Co y Mn z O2, wherein x+y+z=1, the LNCM has the following general formula: Li 1.2 Ni x Co y Mn z O2, in the formula, x+y+z=0.8; 2) mixing the kernel in step 1), nickel salt and manganese salt in a molar ratio of 1:3, ammonium salt, and deionized water, and stirring with ultrasonic until completely dissolved; 3) transferring the mixture solution obtained in step 2) into a reactor for hydrothermal reaction, and obtaining material A after cooling; 4) washing the material A obtained in step 3) in a solution of deionized water and alcohol and drying to obtain a core-coating layer precursor structure, wherein the drying temperature is 80-150° C. and the drying duration is 1-24 hours; 5) adding a lithium source to the product obtained in step 4) and then sintering to obtain a positive electrode active material of a lithium ion battery positive electrode active material having a core-coating layer structure, wherein the coating layer has the following general formula: Li a Ni 0.5 Mn 1.5 O4, wherein 0.5≤a≤1.5, wherein the coating layer is coated on the surface of the inner core.

13. The method according to claim 12, characterized in that The temperature of the hydrothermal reaction in step 3) is 200-250° C. and the duration is 1-48 hours.

14. The method according to any one of claims 12 to 13, characterized in that The sintering temperature of step 5) is 800-1500° C. and the duration is 1-12 hours.

15. The method according to any one of claims 12 to 13, characterized in that The molar ratio of the product of step 5) to the lithium source is 0.75-0.

8.

16. The method according to any one of claims 12 to 13, characterized in that The sintering atmosphere in step 5) is oxygen or air.

17. A lithium ion battery, characterized in that: The invention comprises: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode active material as claimed in any one of claims 1 to 11, or the positive electrode active material prepared by the method as claimed in any one of claims 12 to 16.

18. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode active material as claimed in any one of claims 1 to 11, or the positive electrode active material prepared by the method as claimed in any one of claims 12 to 16.

19. An electrical device, characterized in that: It comprises the lithium ion battery as claimed in claim 17 or the secondary battery as claimed in claim 18.

20. A battery module, characterized in that: It comprises the lithium ion battery as claimed in claim 17 or the secondary battery as claimed in claim 18.

21. A battery pack, characterized in that: It comprises the lithium ion battery as claimed in claim 17 or the secondary battery as claimed in claim 18.

Citation Information

Patent Citations

  • Cathode active material for lithium secondary battery, and cathode and lithium secondary battery comprising the same

    KR1020160050835A

  • Cathode active material for lithium secondary and lithium secondary batteries comprising the same

    KR1020160083638A